GameStop's next play: reconfiguring the value offering. Issue 1 (17th December 2019) - Bass, A. Erin; Pleggenkuhle-Miles, Erin G.; Winchester, Christopher C.; West, Thomas
Abstract : Theoretical basis: The theoretical basis for this case is a focus on strategic positioning as related to Porter's generic strategies. The case describes GameStop's previous differentiation approach, executed through physical stores and knowledgeable staff. With technological shifts and the introduction of digital downloads, this strategy is less effective. The case requires students to consider how GameStop might revise its generic strategy based on the new competitive landscape in which it operates. Research methodology: In writing this case, the research team conducted thorough analysis through primary data collection in stores as well as secondary data collection through the use of market research tools, such as IBIS World, MergentOnline, S&P Net Advantage, and academic journals, trade magazines, and websites. Case overview/synopsis: With high uncertainty shown by stakeholders about the future of GameStop coupled with falling share prices, the company must find a way to stay in play given the rapidly growing digital gaming market. As it planned to close at least 150 of its 7, 500 stores, the company was starting to take measures to reduce operational costs and restructure to sectors that best fit consumer interests. GameStop's core competencies were no longer aligned with market conditions, and its executives were now questioning where it could expand the organization's operations as they focused on finding untapped areas of the market that have an opportunity for a new competitive advantage. Given its unique market share in gaming memorabilia and trade-in values, students are tasked with finding GameStop's existing competitive advantages or identifying potential new ones that can be leveraged in a technology-driven industry. Complexity academic level: This case could be taught at either the graduate or undergraduate level strategy course. At the undergraduate level, it would be best taught when discussing industry life cycle or competitive dynamics. At the graduate level, MBAs could discuss competitive dynamics facing GameStop and how it might find areas for future strategic growth.